Economic Instruments and the Greenhouse Effect - Bertram, L.G; Stephens, R.J; Wallace, C.C (School of Management Working Papers, 1990)
The recent build-up of "greenhouse gases" in the atmosphere means that there is a significant probability of global warming over the coming half-century. This prediction is subject to very great uncertainties concerning both the actual likelihood of warming, its possible magnitude, and the probable effects on the world economy. Faced with these uncertainties, the nations of the world can be expected to adopt some form of minimum-regret response. At this stage, such a response is likely to consist of two elements: an accelerated programme of scientific research, and further steps towards the negotiation of international agreements to deal with the identified problems. The 1987 Montreal Protocol on CFCs and halons has demonstrated the speed with which such agreements can be reached, and the possibility of their effective implementation, once political will is established. The 1988 Toronto conference resolution on first steps towards reducing CO2 emissions over the long run opens the way to debate and negotiation over an international policy regime to tackle Co2, methane, and nitrous oxide emissions. This paper considers four policy options which show promise in the search for a long-run solution to a perceived greenhouse threat. These should be regarded as potentially-complementary, not mutually-exclusive, elements in a total policy package. The options are: (a) a system of tradeable emission permits or entitlements, issued by an international agency and exchanged through an open international marketplace; (b) a system of detailed quantitative e mission permits enforceable in international law; (c) a system of taxes or levies targeted at emissions or at consumption of specified fuels; (d) a convention setting ambient standards to be met on a country-by-country basis, and legitimating international sanctions against offending countries.